Hermeneutika al-Qur'an ala pesantren - Burhanuddin, Mamat S. (UII Press, 2006)
Analysis on the Koranic intepretation by Nawawi Banten, an ulama from East Java Analysis on the Koranic interpretation by Nawawi Banten, an ulama from East Java
Includes bibliographical references (p. 219-227) and index
Keywords: Nawawi Banten